2016
DOI: 10.2174/1874303x01609010051
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function and Correlates in Women Undergoing Maintenance Hemodialysis in Cameroon: A Multi-centric Study

Abstract: Purpose of The Study:The aim of this study was to describe sexual function disorders and investigate associated factors in women on maintenance hemodialysis in Cameroon. Methods:This was a cross-sectional study of three months duration (August-October 2014) in adult women on maintenance hemodialysis (HD) at three HD facilities in Cameroon. Patients with active psychiatric disease, infection or uncontrolled congestive heart failure were excluded. We use the Rosen questionnaire for evaluating female sexual funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Sexual dysfunction is multi-faceted and includes increasing age, menopausal status, depression, and comorbidities like diabetes and hypertension as its major predictors. Literature also shows a discrepancy in the relationship between older age and depression with sexual functioning [ 17 , 18 ]. In particular, the results of this study manifested that age had a significant negative correlation with sexual desire, but not with arousal, lubrication, orgasm, satisfaction, or pain.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual dysfunction is multi-faceted and includes increasing age, menopausal status, depression, and comorbidities like diabetes and hypertension as its major predictors. Literature also shows a discrepancy in the relationship between older age and depression with sexual functioning [ 17 , 18 ]. In particular, the results of this study manifested that age had a significant negative correlation with sexual desire, but not with arousal, lubrication, orgasm, satisfaction, or pain.…”
Section: Discussionmentioning
confidence: 99%
“…These disorders were positively correlated with personal medical histories, including data about nephropathy, duration of hemodialysis greater than or equal to one year, depression, anxiety, and effects on quality of life. This is supported by a study by Teuwafeu et al (2016), who reported that all women with maintenance hemodialysis have at least one sexual function abnormality, including sexual dysfunction and sexual inactivity. Sexual dysfunction included: decreased sexual desire, decreased sexual arousal, decreased vaginal lubrication, and failure to achieve orgasm.…”
Section: Discussionmentioning
confidence: 52%
“…According to the present study findings, for the majority of women in the sample, more than half of their menstrual cycles were irregular, a finding supported by the study of Abozead et al (2018), which reported that the majority of female patients with hemodialysis were still menstruating. With respect to this, the study by Teuwafeu et al (2016) on Sexual function and correlates in women undergoing maintenance hemodialysis in Cameroon showed that women of child-bearing age reported menstrual disorders such as irregular menses, amenorrhea, oligomenorrhea, poly-menorrhea, metrorrhagia, and menorrhagia. Conversely, Basok et al (2009) found that more than half of women with hemodialysis had gone through menopause.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We could not find any study that evaluates the relationship of blood indices in IDA and sexual function. However, Teuwafeu et al, in their study on women who underwent maintenance hemodialysis found that there is a significant relationship between anemia and sexual function [38].…”
Section: Resultsmentioning
confidence: 99%